Effects of supervised and unsupervised skipping rope training on perceptual responses among recreational badminton players - Lin, Liow Kai (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The global outbreak of Covid-19 has spread in Malaysia, social and physical distancing measures, lockdowns of businesses, schools and overall social life have disrupted many regular aspects of life, including sport and physical activity. Many individuals and athletes are not able to actively participate in their regular individual or group sporting activities. Under such conditions, it leads less physically active and hence resulting in weight gain and loss of physical fitness. Recently, skipping rope exercise is getting popular and has been shown to elicited positive effect on health-related fitness and specific-related fitness across multiple populations (e.g., athletes, adolescents and overweight). However, the perceptual responses (e.g., affective responses, enjoyment, and perceived exertion) of supervised and unsupervised skipping rope training is not well documented. Hence, the purpose of this study is to determine the effects of supervised vs unsupervised skipping rope training on perceptual responses among recreational badminton players. A total of twenty recreational badminton player with more than oneyear badminton experienced (n=20, 5 males and 15 females, age = 22.80 ± 0.89 years) were recruited in this randomised and parallel study. Participants were randomly assigned into two groups, namely supervised group (SG) and unsupervised group (UG). This training program was carried out three times per week for four weeks (a total 12 sessions). During each exercise session, participants performed warming up for five minutes, followed by 60-75 jump repetitions separated by one minute recovery interval and ended with cooling down for five minutes. All the dependent variables including heart rate (HR), exercise enjoyment scale (EES), feeling scale (FS), felt arousal scale (FAS) and rate of perceived exertion (RPE) were recorded before, during and after each session. Data were analysed using a mixed model of variance (ANOVA) was performed to examine differences in all dependent variables between groups over training session (sessions 3,6,9, and 12). The results showed that there were significant increases in FS (p = 0.03) and RPE (p = 0.027) between supervised and unsupervised group following four weeks of skipping rope training. Affective responses measured by FS were greater during SG compared to UG across all sessions meanwhile perceived exertion responses measured by RPE were higher in UG compared to SG across all sessions. However, it showed no significant changes in HR (p = 0.77), FAS (p = 0.69) and EES (p = 0.74). Thus, in conclusion, this study showed that SG elicited better feeling than UG in every session while UG elicited greater RPE than SG in every session. Further studies are needed for in depth understanding of the perceptual responses between supervised and unsupervised intervention method.